64-Slice CT compared to MRI to clear cervical spine injury in high-risk GCS < 14 blunt trauma patients admitted to the ICU. (January 2018) - McCallum, Jessica; McLaughlin, Patrick; Hameed, Morad; Kanji, Hussein D
Objective: Clearance of cervical spine injury including ligamentous injury is of paramount importance as results of missed injury may have serious consequences. In obtunded patients, cervical spine clearance is challenging. This study sought to determine whether a negative 64-slice CT scan alone is sufficient to clear cervical spine injury. Patients and methods: All consecutive blunt trauma patients admitted to a regional (level 1) trauma center from 1 April 2008 to 31 March 2012 were screened for inclusion in this study. High-risk, GCS < 14, blunt trauma patients were included if they were admitted to the intensive care unit, had a negative 64-slice CT, and MRI of diagnostic quality. GCS was measured at the time of CT scan. Patients with a positive finding on CT scan were excluded. All images were re-interpreted by a trauma radiologist blinded to clinical outcome. Details of missed injuries and clinical impact were reported. The primary outcome was missed clinically significant injury, defined as any injury requiring an additional intervention including continued immobilization or surgery. Results: There were 5891 blunt trauma patients admitted to the ICU, 44 of whom met inclusion criteria. Patients had a median injury severity score of 35 and MRI three (2–9) days after CT. Eight of 44 (18%) patients had a positive finding on MRI and five of the findings were clinically insignificant. Three patients (7%) with focal neurologic findings on clinical exam had missed injuries requiring immobilization with a collar. Two of these patients had spine disease, which may have increased their injury risk. Conclusions: In high-risk obtunded blunt trauma patients admitted to the ICU, a negative 64-slice CT scan alone is insufficient to clear clinically significant cervical spine injury, with a missed clinically significant injury rate of 7%. When considered with symmetric motor function, a negative 64-slice CT scan may be sufficient. A prospective study is required to confirm these findings.